2016
DOI: 10.1002/1873-3468.12441
|View full text |Cite
|
Sign up to set email alerts
|

OB or Not OB: Idiosyncratic utilization of the tRNA‐binding OB‐fold domain in unicellular, pathogenic eukaryotes

Abstract: In this review, we examine the so-called OB-fold, a tRNA-binding domain homologous to the bacterial tRNA-binding protein Trbp111. We highlight the ability of OB-fold homologs to bind tRNA species and summarize their distribution in evolution. Nature has capitalized on the advantageous effects acquired when an OB-fold domain binds to tRNA by evolutionarily selecting this domain for fusion to different enzymes. Here, we review our current understanding of how the complexity of OB-fold-containing proteins and enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…MPsome proteins (Fig 6,Tables S3 and S4) suggests that they have some similar functional characteristics which may aid elucidating their specific functions. Variants of the ZF, IDR and OB-fold domains of A3 function in a wide range of critical processes that entail protein and nucleic acid interactions which span DNA replication, repair and telomere maintenance as well as transcription, tRNA and microRNA processing, translation and others (Allison et al 1998;Brevet et al 2003;Theobald et al 2003;Horvath 2011;Nam et al 2011;Kapps et al 2016;Wang et al 2017;Amir et al 2018;Gao et al 2018). Results from this study may contribute the understanding of the roles of these domains in RNA editing and other processes.…”
Section: Scsmentioning
confidence: 82%
“…MPsome proteins (Fig 6,Tables S3 and S4) suggests that they have some similar functional characteristics which may aid elucidating their specific functions. Variants of the ZF, IDR and OB-fold domains of A3 function in a wide range of critical processes that entail protein and nucleic acid interactions which span DNA replication, repair and telomere maintenance as well as transcription, tRNA and microRNA processing, translation and others (Allison et al 1998;Brevet et al 2003;Theobald et al 2003;Horvath 2011;Nam et al 2011;Kapps et al 2016;Wang et al 2017;Amir et al 2018;Gao et al 2018). Results from this study may contribute the understanding of the roles of these domains in RNA editing and other processes.…”
Section: Scsmentioning
confidence: 82%
“…We also found that a few Microgenomates lysyl-tRNA synthetases (KKR67068.1 & KKQ91124.1) have an additional C -terminal domain that is very similar to this B2 domain and predicted α-helix. It is known that aaRS proteins are often fused with an OB domain [41]. The two Klosterneuburg active sludge metagenomic contigs containing the B2-TyrRS fusion genes showed almost identical gene organization and gene sequences, indicating that these two contigs belong to two closely-related bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…S4 ; Supplemental Tables S4, S5 ) suggests that they have some similar functional characteristics which may aid elucidating their specific functions. Variants of the ZF, IDR, and OB-fold domains of A3 function in a wide range of critical processes that entail protein and nucleic acid interactions which span DNA replication, repair and telomere maintenance as well as transcription, tRNA and microRNA processing, translation, and others ( Allison et al 1998 ; Brevet et al 2003 ; Theobald et al 2003 ; Horvath 2011 ; Nam et al 2011 ; Kapps et al 2016 ; Wang et al 2017 ; Amir et al 2018 ; Gao et al 2018 ). Results from this study may contribute the understanding of the roles of these domains in RNA editing and other processes.…”
Section: Discussionmentioning
confidence: 99%